2018
DOI: 10.2136/sssaj2018.03.0093
|View full text |Cite
|
Sign up to set email alerts
|

Soil Specific Surface Area Determination by Visible Near‐Infrared Spectroscopy

Abstract: The soil specific surface area (SSA) affects soil physical and chemical properties. Numerous studies applied visible near-infrared spectroscopy (Vis-NIRS) to estimate clay content (particles < 2 µm). Since SSA is better defined and more directly related to particle size distribution and mineralogy than clay content, predictions of SSA from Vis-NIRS are expected to be better than that for clay. Thus, the aims of this study were to (i) test the feasibility of using Vis-NIRS for SSA determination, (ii) compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…High R 2 values (>.89) were obtained for all SSA estimations. The SSA EGME validation results exhibit higher accuracy than obtained in Knadel et al, 2018 (SRMSE = 0.13), who validated with a set representing a smaller range of SSA EGME values (4-116 m 2 g −1 ), but also lower SD values (SD = 27) than the validation set used in this study (range: 10-392 m 2 g −1 , SD = 94) ( Table 1).…”
Section: Full Datasetmentioning
confidence: 68%
See 2 more Smart Citations
“…High R 2 values (>.89) were obtained for all SSA estimations. The SSA EGME validation results exhibit higher accuracy than obtained in Knadel et al, 2018 (SRMSE = 0.13), who validated with a set representing a smaller range of SSA EGME values (4-116 m 2 g −1 ), but also lower SD values (SD = 27) than the validation set used in this study (range: 10-392 m 2 g −1 , SD = 94) ( Table 1).…”
Section: Full Datasetmentioning
confidence: 68%
“…However, the application of vis-NIRS to SSA determination is still relatively rare. The few successful attempts to determine the SSA from vis-NIR spectra included the predictions of SSA obtained from the EGME method only (Ben-Dor & Banin, 1995;Ben-Dor, Heller, & Chudnovsky, 2008;Knadel et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these approaches, promising techniques such as spectroscopy in the visible (VIS) and near-infrared (NIR) spectroscopy have been used as proximal sensing techniques and enable the measurement of texture. Indeed, soil components are sensitive to these portions of the electromagnetic spectrum, which allow the assessment of soil textural composition [9]. Curcio et al [10] have predicted soil texture (sand, clay, and silt) using VNIR-SWIR band reflectance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The required preparation for this method is simple, involving only air‐drying of the soil and sieving down to 2 mm. Visible near‐infrared spectroscopy has been successfully used to predict soil properties such as the complete soil texture distribution (Hermansen et al, 2017), soil structure (Katuwal et al, 2018), and soil specific surface area (Ben‐Dor et al, 2008; Knadel et al, 2018). Furthermore, studies have shown its ability to predict the wet part of the soil‐water retention curve (Babaeian et al, 2015; Pittaki‐Chrysodonta et al, 2018; Santra et al, 2009).…”
mentioning
confidence: 99%